Feasibility analysis of solar water heaters for residential use in Trinidad and Tobago / Vishala Hosein ... [et al.] - Hosein, Vishala; Cumberbatch, Edward; Boodlal, Donnie; Maharaj, Rean (Penerbit PRESS, Universiti Teknologi MARA, 2024)
In this study, Electric Water Heater (EWH) and Solar Water Heater (SWH) systems were designed and simulated using the Polysun software and their performances were compared. The EWH and SWH both incorporated a 200 L or 53-gallon storage tank utilizing an auxiliary electrical heating element of 4 kW and 2 kW respectively. The SWH configuration included a 3 m2 solar collector facing South at a 45° tilt angle which achieved an annual total global irradiance of 2,842 kWh on collector aperture area, an average yearly collector efficiency of 52.6%, and an annual average solar fraction of 54%. The yearly total electricity requirement for Domestic Water Heating (DWH) was calculated to be 2,777 kWh and 1,339 kWh using the EWH and SWH respectively, resulting in a 52% SWH savings per year. With a DHW temperature set at 50˚C, the EWH has an estimated value of 1,943.9 kg CO2 per year emissions compared to 937.3 kg CO2 per year associated with the SWH. The use of the SWH can result in an annual savings of TT$ 458.91. Using the current subsidized electricity rate at US$ 0.047 per kWh and the 100% tax credit on the cost of a SWH, the Simple Payback Period (SPP) of the SWH was approximately seven years. When the researchers considered the government's proposed electricity rate increase of 40-65.75%, followed by the complete removal of the subsidy, the researchers observed that the Simple Payback Period (SPP) for the SWH system was reduced to approximately 4 to 5 years and 1.5 to 2 years, respectively. This study has demonstrated the economic and environmental feasibility of SWH use in Trinidad and Tobago as the Government moves to achieve its Nationally Determined Commitments (NDCs).